Antitumor and Radiosensitization Effects of a CXCR2 Inhibitor in Nasopharyngeal Carcinoma - Liu, Xiaobei; Lan, Tianxia; Mo, Fei; Yang, Jingyun; Wei, Yuquan; Wei, Xiawei (Frontiers in Cell and Developmental Biology, 2021)
CXCR2, a member of the G-protein-coupled cell surface chemokine receptor family, is commonly found on leukocytes, endothelial cells and tumour cells including nasopharyngeal carcinoma cells. However, how the activity of CXCR2 and its ligand CXCL8 aﬀects the development of nasopharyngeal carcinoma (NPC) remains unknown. Here, we found that CXCR2 and CXCL8 were both predicted poor prognosis in NPC patients. Furthermore, we identified that treatment with CXCR2 antagonist SB225002 of nasopharyngeal carcinoma cell lines resulted tumorigenesis inhibition in vitro and in vivo. In addition, we found that SB225002 could enhance NPC cells radiosensitivity through regulating cell circle distribution and interfering with cellular DNA damage repair. SB225002 also exhibited an efficient radiosensitization eﬀect in C666-1 and HONE-1 bearing mice. Functionally, we showed that SB225002 reduced microvessel density and proliferation and induced tumour apoptosis. Furthermore, changes in the tumour microenvironment were also observed in this study. We observed that SB225002 reduced tumour-associated neutrophils (TANs) in the tumours tissue which were recruited especially after irradiation. Taken together, our results suggested that targeting the CXCL8-CXCR2 pathway is a promising therapeutic strategy for comprehensive NPC treatment.